A phenoxo-bridged dicopper(ii) complex as a model for phosphatase activity: mechanistic insights from a combined experimental and computational study12. Issue 12 (8th March 2017) - Barman, Suman K.; Mondal, Totan; Koley, Debasis; Lloret, Francesc; Mukherjee, Rabindranath
Abstract : Hydrolysis of RNA-model substrate HPNP by a dicopper(ii ) complex has been studied with combined experimental and theoretical approach. Involvement of H-bonding has been probed by DFT calculations. Abstract : A μ-phenoxo-bis(μ2 -1, 3-acetato)-bridged dicopper(ii ) complex [CuII2(L 1 )(μ-O2 CMe)2 ][NO3 ] (1 ) has been synthesized from the perspective of modeling phosphodiesterase activity. Structural characterization was done initially with1 ·3Et2 O (vapour diffusion of Et2 O into MeOH solution of1 ; poor crystal quality) and finally with its perchlorate salt [CuII2(L 1 )(μ-O2 CMe)2 ][ClO4 ]·1.375MeCN·0.25H2 O, crystallized from vapour diffusion of n -pentane into a MeCN–MeOH mixture (comparatively better crystal quality). An asymmetric unit of such a crystal contains two independent molecules of compositions [CuII2(L 1 )(μ-O2 CMe)2 ][ClO4 ] and [CuII2(L 1 )(μ-O2 CMe)2 (MeCN)][ClO4 ] (coordinated MeCN with 0.75 occupancy), and two molecules of MeCN and H2 O (each H2 O molecule with 0.25 occupancy) as the solvent of crystallization. These two cations, each having five-coordinate (μ-phenoxo)bis(μ-acetato)-bridged Cu II ions, differ by only the coordination environment of only one Cu II ion, which has a weakly coordinated acetonitrile molecule in its sixth position. Temperature-dependent magnetic studies on1 reveal that the copper(ii ) centres are antiferromagnetically coupled with the exchange-coupling constant J = −124(1) cm −1 . Theoretically calculated J = −126.51 cm −1, employing a broken-symmetry DFT approach, is in excellent agreement with the experimental value. The dicopper(ii ) complex has been found to be catalytically efficient in the hydrolysis of 2-hydroxypropyl- p -nitrophenylphosphate (HPNP). Detailed kinetic experiments and solution studies (potentiometry, species distribution and ESI-MS) were performed to elucidate the reaction mechanism. DFT calculations were performed to discriminate between different possible mechanistic pathways. The free-energy barrier for HPNP hydrolysis catalyzed by1 is comparable to that obtained from the experimentally-determined value. The involvement of non-covalent (hydrogen-bonding) interaction has also been probed by DFT calculations. The activity of1 is found to be the highest, compared to the structurally-characterized MnII2, CoII2, NiII2 and ZnII2 complexes of L 1 (−) reported earlier, under identical experimental conditions, in which each metal centre is six-coordinate.